Study of antibacterial and mechanical properties of poly(methyl methacrylate‐co‐acrylic acid)/hydroxyapatite biocomposite by using artificial neural network approach - Deepti Rekha Sahoo; Trinath Biswal (SPE Polymers, 2024)
Abstract A novel, promising biocomposite was synthesized through the free radical polymerization method using methyl methacrylate (MMA), acrylic acid (AA), and hydroxyapatite derived from oyster shells (Os‐HA). Fourier transform infrared spectroscopy (FTIR) peaks indicate the conjugation of Os‐HA in the biocomposite. From the TGA analysis, it was observed that a weight loss of nearly 2% is achieved at 210°C, up to 15% at 210 to 420°C, and up to 95% at 420 to 580°C. The SEM image shows the uniform dispersion of the Os‐HA particles and strong interaction with the copolymer matrix. The broad spectrum at 2θ = 14.6° in XRD analysis indicates the amorphous nature of poly(MMA‐co‐AA)/Os‐HA. The higher inhibition zone of the biocomposite is observed at 125 μL against E. coli bacteria. The maximum water absorption is observed at 15 wt% of Os‐HA. The young's modulus gradually increases, while the impact strength decreases up to 20 wt% of Os‐HA. The artificial neural network (ANN) model has been used to assess the optimum values of impact strength, tensile strength, and Young's modulus of the biocomposite material. The correlation factor (R = 0.998) of the ANN model data indicates greater accuracy of the experimental result.